PETROLOGY AND GEOCHEMISTRY OF GEDE-SALAK VOLCANO BANTEN PROVINCE, INDONESIA - Andri Kurniawan, Idham
Gede-Salak volcano is located in the Banten Province, Serang, North West Java. This volcano is consisted of several volcanoes which are Gede, Salak, Batur, Wadas, Peda, Batu and Kedepel. Field mapping show suggests that the geological formation of Gede-Salak volcano can be divided into two stages. The pra-caldera stage is consisted of lava Batu volcano, lava Gede volcano and lava Salak volcano. The pasca-caldera stage is formed by pyroclastic flows deposits Batur volcano, lava dome Kedepel and Wadas and lava dome Peda. Petrography analysis of lava has similar characteristics which is porphyritic texture but can be distinguished based on the composition of phenocrysts, which are: Batu volcano lava is andesite hyperstene - augite; Gede volcano lava is basaltic andesite; Salak volcano lava is andesite; Kedepel and Wadas volcanic lava domes is andesite hornblende and Peda volcano lava dome is andesite augite. Oscillatory zoning and opaque rim in hornblende are observed, which are related to the process of magmatism. Classification of volcanic rocks based Harker and A-F-M diagram classified that volcanic rock of Gede-Salak volcano have Calc-alkaline affinity. This is confirmed by K2O vs SiO2 diagram that show Gede-Salak volcanic rocks in the pra-caldera and pasca-caldera stage is included into the medium-K calc alkaline and high-K calc alkaline. Results of analysis spider diagram, normalized to chondrite, primitive mantle and MORB, lava rock in Gede-Salak volcano has a relatively similar pattern, revealing a pattern indicating magma arc intermediates in the continent arc. The existence of several elements that are Pb and Ce anomaly indicating magmatism process is affected by subduction components. Petrogenesis processes that occur viewed in petrography and geochemical character are (a) the occurrence of magma mixing process or asimilation, (b) have loss of pressure in the initial phase of Gede-Salak volcano eruption, (c) contained Pb and Ce anomalies that indicate the magmatism process is influenced by sediment or water and (d) comparison of the ratio element B indicates that the subduction component affects to magmatism process in Gede-Salak volcano. Comparison of Gede-Salak volcano characters plus Pinang and Rawa Danau volcano as a group of North West Java (NWJ) to regional in Java Island, that are West Java (WJ) and Central Java (CJ) shows: (1) Comparison of element ratios Ba / Zr and Nb / Zr obtained NWJ and WJ magmatisme process is almost the same and closer to MORB, whereas for the CJ is very different, the process is more influenced by components subduction. In addition of two patterns that indicates the source magmatism derived from OIB. (2) The ratio of the element B with La and Nb into the Beniof zone show the value of ratio in CJ greater than NWJ, this is indicates that the amount of subduction component in the CJ more influential than NWJ. The interpretation to the subduction process is the subduction angle of CJ is steeper than NWJ.